2013
DOI: 10.1111/cen.12163
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone and arterial dysfunction in the multi‐ethnic study of atherosclerosis

Abstract: Objective High circulating concentrations of parathyroid hormone (PTH) have been associated with increased risks of hypertension, left ventricular hypertrophy, congestive heart failure, and cardiovascular mortality. Impaired arterial function is a potential mechanism for these associations. We tested whether serum PTH concentration is associated with measures of arterial function. Design Cross-sectional study. Participants 6,545 persons without clinical cardiovascular disease participating in the community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 39 publications
(55 reference statements)
3
49
1
3
Order By: Relevance
“…This suggestion would suggest a biological role for PTH in promoting symptoms of HF and consequently BNP expression, 7,14,15,37,38 but this is speculative. PTH has been associated with NT-proBNP in this and other studies.…”
Section: Pth and Incident Hfmentioning
confidence: 99%
“…This suggestion would suggest a biological role for PTH in promoting symptoms of HF and consequently BNP expression, 7,14,15,37,38 but this is speculative. PTH has been associated with NT-proBNP in this and other studies.…”
Section: Pth and Incident Hfmentioning
confidence: 99%
“…PTH may therefore serve a role in the pathophysiology of cardiovascular disease (13). A series of previous studies (14,15) have suggested that PTH may directly induce endothelial dysfunction and contribute to VC. However, the underlying mechanisms of this remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 In a sample of more than 3000 individuals free from major cardiovascular with a wide range of ages (mean age of 62 years), researchers from MESA showed positive association of PTH with arterial stiffness measured by aortic pulse pressure. However, the Health ABC study, which has an older population with a mean age of 72 years, did not find any association between PTH and aortic pulse wave velocity.…”
Section: Discussionmentioning
confidence: 99%